You're so Vane (You Probably Think This is About You): The Provenance of the Dave Redmon Postcard Collection - Page, Griffin (Kansas State University, The Chapman Center for Rural Studies, 2016)
If we are fortunate in life, we may make a discovery that alters the face of human existence and society. The Historic Redmon Postcard Collection is not one of those discoveries. But nonetheless, it does provide a unique insight into early 20th Century America. In March, 2014, Chapman Center for Rural Studies received the gift of 301 postcards, a single preserved collection.
Griffin Page, “You're so Vane (You Probably Think This is About You): The Provenance of the Dave Redmon Postcard Collection,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/240.
Keywords: Pittsburg Morning Sun; Dave Redmon; Parsons; Postcard collection; Lawrence; Harold Vane Brown